Micronodular T-cell/histiocyte-rich B-cell lymphoma of the spleen in a case of small lymphocytic lymphoma: A Richter's transformation - TÜRKÖZ, HÜSEYİN KEMAL (INFORMA HEALTHCARE, 2010)
A case of micronodular T-cell/histiocyte- rich B-cell lymphoma of the spleen who had a prior diagnosis of small lymphocytic lymphoma is presented. Micronodular T-cell/histiocyte- rich B-cell lymphoma of the spleen was first described in 2003, and very few cases have been reported since then. This is the first reported case supervening in a patient with pre-existing chronic lymphocytic lymphoma. We review its clinical, pathologic, and immunohistochemical features and the difficulties we encountered during diagnosis.
Keywords: Large B-cell lymphoma; spleen; T-lymphocytes; MARGINAL ZONE LYMPHOMA